2021
DOI: 10.1097/md.0000000000025218
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of macrophage-colony stimulating factor-1 receptor as a prognostic factor for survival in cancer

Abstract: Background: The relation between the expression of macrophage-colony stimulating factor-1 receptor (CSF-1R) and prognosis of cancer patients has been evaluated in multiple studies, but the results remain controversial. We, therefore, performed a meta-analysis and systematic review to figure out the role of CSF-1R in the prognosis of patients with cancer. Methods: Several databases were searched, including Web of Science, PubMed, and EMBASE. All human studies were publis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 57 publications
0
5
0
Order By: Relevance
“…Under physiological conditions, CSF-1 is produced by fibroblasts, endothelial cells, monocytes, macrophages, osteoblasts, microglia, keratinocytes, bone marrow stromal cells, natural killer cells, B-cells and T-cells and epithelial cells [65,66]. It is an essential regulator of development and homeostasis of the mononuclear phagocyte system and, by extension, a key factor of CSF1-dependent macrophage control of development and homeostasis [64,67,68]. CSF-1 appears to play an autocrine and/or paracrine role in cancers of the ovary, endometrium, breast, lung, the nervous system, and myeloid and lymphoid tissues, within which overexpression of CSF-1 receptor is considered as a prognostic factor for survival in cancer [68].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Under physiological conditions, CSF-1 is produced by fibroblasts, endothelial cells, monocytes, macrophages, osteoblasts, microglia, keratinocytes, bone marrow stromal cells, natural killer cells, B-cells and T-cells and epithelial cells [65,66]. It is an essential regulator of development and homeostasis of the mononuclear phagocyte system and, by extension, a key factor of CSF1-dependent macrophage control of development and homeostasis [64,67,68]. CSF-1 appears to play an autocrine and/or paracrine role in cancers of the ovary, endometrium, breast, lung, the nervous system, and myeloid and lymphoid tissues, within which overexpression of CSF-1 receptor is considered as a prognostic factor for survival in cancer [68].…”
Section: Discussionmentioning
confidence: 99%
“…It is an essential regulator of development and homeostasis of the mononuclear phagocyte system and, by extension, a key factor of CSF1-dependent macrophage control of development and homeostasis [64,67,68]. CSF-1 appears to play an autocrine and/or paracrine role in cancers of the ovary, endometrium, breast, lung, the nervous system, and myeloid and lymphoid tissues, within which overexpression of CSF-1 receptor is considered as a prognostic factor for survival in cancer [68].…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, the autophosphorylation of the CSF-1R signaling pathway is effectively inhibited by PLX3397, resulting in the inhibition of the downstream signaling molecules PI3K, AKT, ERK, and RAF, which affect tumor cell function. 18 , 19 In vivo studies found that pexidartinib/PTX treatment led to a remarkable reduction in CD31 + vascular density within mammary tumors and induced apoptosis and necrosis of tumor cells in the MMTV-PyMT mouse model of breast cancer. 7 To date, preclinical studies on the antitumor effects of PLX3397 have been conducted in hepatocellular carcinoma, cervical cancer, and melanoma.…”
Section: Introductionmentioning
confidence: 99%
“…CSF1R is responsible for cancer cell proliferation, invasion and survival [15][16][17][18][19][20][21]. CSF1R is strongly related to poor outcomes and contributes to tumor cell invasiveness and pro-metastatic behavior [12,15,18,[22][23][24][25][26]. Pexidartinib, a pyrrolopyridine-based compound, is the first FDA-approved CSF1R tyrosine kinase inhibitor [27,28].…”
Section: Introductionmentioning
confidence: 99%